2021
DOI: 10.1038/s41598-021-02267-2
|View full text |Cite
|
Sign up to set email alerts
|

Blood phenylalanine reduction reverses gene expression changes observed in a mouse model of phenylketonuria

Abstract: Phenylketonuria (PKU) is a genetic deficiency of phenylalanine hydroxylase (PAH) in liver resulting in blood phenylalanine (Phe) elevation and neurotoxicity. A pegylated phenylalanine ammonia lyase (PEG-PAL) metabolizing Phe into cinnamic acid was recently approved as treatment for PKU patients. A potentially one-time rAAV-based delivery of PAH gene into liver to convert Phe into tyrosine (Tyr), a normal way of Phe metabolism, has now also entered the clinic. To understand differences between these two Phe low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…2 A ), suggesting that aspartame’s effects may extend beyond the glutamate-GABA axis and involve dopaminergic signaling in the amygdala. Aspartame’s effects on dopamine could occur as a result of increases in plasma and brain concentrations of phenylalanine ( 3 5 , 11 , 69 71 ), another metabolite of aspartame. However, since our focus was on the glutamatergic and GABAergic neurotransmission, we did not pursue further the changes in dopaminergic synapse pathway.…”
Section: Discussionmentioning
confidence: 99%
“…2 A ), suggesting that aspartame’s effects may extend beyond the glutamate-GABA axis and involve dopaminergic signaling in the amygdala. Aspartame’s effects on dopamine could occur as a result of increases in plasma and brain concentrations of phenylalanine ( 3 5 , 11 , 69 71 ), another metabolite of aspartame. However, since our focus was on the glutamatergic and GABAergic neurotransmission, we did not pursue further the changes in dopaminergic synapse pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that with the reduction in cost and wide application of NGS, newborn genetic screening has recently received more attention [ 121 125 ]. Multiple studies have assessed the effect of HPA on liver functions in PKU in mice using transcriptome and proteomic analyses [ 126 ].…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…Another potential therapy (currently in clinical trials Phase 1/2) consists of a single delivery of a rAAV carrying the PAH gene directly into liver to convert Phe into tyrosine, mimicking the normal process of Phe metabolism. In 2021, Manek et al [ 80 ] performed transcriptomic and proteomic analyses in order to compare these two Phe-lowering strategies. They found that both approaches lower brain Phe and increase neurotransmitter levels, thereby correcting animal behavior.…”
Section: Proteomics For the Study Of Imdmentioning
confidence: 99%